Progressive Muslims: On Justice, Gender, and Pluralism by Omid Safi, ed. (Oxford: Oneworld, 2003. 351 pages.) (American Journal of Islam and Society, 2005)
Particularly since 9/11, students and the wider public have been asking NorthAmerican Muslim academics to comment on current events, while Muslimstudents and the larger Muslim community tend to expect Muslim academicsto “defend Islam” by engaging in apologetics. Nonetheless, this book beginsby stating that its authors seek to raise the level of discourse about Islam, andwant to avoid both apologetics and simplistic answers to complex questions.The introduction makes frank observations about the present state ofthe world’s Muslims and calls for an intellectual response that seriouslyengages modern realities. It is followed by fourteen chapters, which aredivided into three sections, which deal with contemporary interpretations ofIslam, gender issues, and pluralism, respectively. The book concludes witha suggested further reading list and an index ...